The contribution of cultural identity to subjective well-being in collectivist countries: a study in the context of contemporary Chinese culture - Zhou, Song; Liu, Gaoyu; Huang, Yingming; Huang, Tingyu; Lin, Shiya; Lan, Jie; Yang, Huaqi; Lin, Rongmao (Frontiers in Psychology, 2023)
Introduction Though the important effect of cultural identity on subjective well-being is widely acknowledged, the details of how different cultures’ unique features influence well-being remain to be revealed. To address this issue in the context of Chinese culture, the present study investigates whether and how the prominent features of Chinese culture—collectivism and red culture—shape Chinese people’s subjective well-being. Methods The Red Cultural Identity Scale, Subjective Well-Being Scale, Collectivism Scale, and Perspective-Taking Scale were used to assess 1,045 Chinese residents. Results The results showed that red cultural identity positively predicted participants’ subjective well-being through the mediated role of collectivism. Furthermore, perspective-taking was found to moderate the mediating effect of collectivism. Discussion These results demonstrate that the way cultural identity predicts subjective well-being is highly correlated to specific cultural features, e.g., the opinion of values, which was significant in practice with a cross-cultural background.